Kepastian Hukum terhadap Tindak Pidana Pencemaran Nama Baik melalui Media Elektronik Berdasarkan Peraturan Perundang-Undangan (SETARA : Jurnal Ilmu Hukum, 2022)
This article examines legal certainty and legal protection for victims of defamation committed through electronic media in Indonesia. The study is motivated by the rapid expansion of social media use, the high frequency of online defamation cases, and the continuing controversy over the use of Article 27 paragraph (3) of the Electronic Information and Transactions Law. Using normative juridical research with statutory and conceptual approaches, the article analyzes the relationship between the Criminal Code, the Electronic Information and Transactions Law, and broader constitutional guarantees of legal certainty and protection of dignity. The study finds that the existing framework formally provides a legal basis for addressing online defamation, but its implementation still raises concerns of overcriminalization, inconsistent interpretation, and weak protection for victims and freedom of expression at the same time. The article argues that legal certainty requires clearer interpretive limits, while legal protection for victims requires balanced enforcement that safeguards reputation without turning criminal law into a tool of disproportionate repression.